Revealing the Students’ Self-Regulated Learning Levels During the Covid-19 Outbreak: a Single Case Study in Jakarta (Indonesian Journal of Curriculum and Educational Technology Studies, 2021)
This study aims to identify the level, describe and analyze the self-regulated learning of class XI students during the COVID-19 pandemic at SMAN 63 Jakarta. The research method used quantitative descriptive with a survey design. The technique of collecting data through the MSLQ Likert learning strategies subscales by Pintrich 1991 with total technic sampling. The results showed that the self-regulated learning conducted by XI students during the covid-19 pandemic is in the moderate category with an empirical mean of 54.29 and a standard deviation of 6,933. The conclusion of this research is all of the students in class XI who tend to have the ability to manage resource management strategies are in the medium category. All indicators of resource management strategy were time management and learning environment (52.7%), effort regulation (67.3%), peer learning (62.4%), and help-seeking (53.7%). Abstrak Penelitian ini bertujuan untuk menggambarkan tingkatan, mendeskripsikan dan menganalisis self-regulated learning siswa kelas XI pada masa pandemi covid-19 di SMAN 63 Jakarta. Metode penelitian yang digunakan adalah metode penelitian kuantitatid deskriptif dengan desain penelitian survei. Teknik pengumpulan data menggunakan subskala learning strategies The MSLQ Scales karya Pintrich 1991 dengan teknik total sampling. Hasil penelitian menunjukkan bahwa self-regulated learning yang dilakukan siswa kelas XI pada masa pandemic Covid-19 berada pada kategori sedang dengan mean empiris sebesar 54.29 dan standar deviasi sebesar 6.933. Simpulan dari penelitian ini adalah seluruh siswa kelas XI cenderung memiliki kemampuan berdasarkan resource management strategies berada pada kategori sedang. Indikator dari resource management strategies adalah time and study environment (52.7%), effort regulation (67.3%), peer learning (62.4%), dan help seeking (53.7%).